Avaliação do processamento auditivo e da linguagem em pacientes com neurofibromatose tipo 1 - Pollyanna Barros Batista (2011)
Introduction: High prevalence of learning disabilities resulting in poor academic performance has already been described in Neurofibromatosis type 1. Learning process depends on the ability to listen, understand and separate the relevant parts of speech from background noise, regardless of the physical environment. It is known that much of the language is learned by hearing which is considered a functional system responsible for receiving sound information and convert them into specific transduction signals along the nerve fibers to the cortex. When there is a weak performance in one or more auditory abilities, it is much more difficult to learn without special assistance, even with normal intelligence, motivation and health. Objectives: Verify the neurological processing of the auditory information and its possible association with language and learning disabilities in patients with NF1. Methods: Descriptive-comparative study with 25 patients with NF1 (14 female and 11 male) and 22 controls (15 female and 7 male) aged 10 to 34 years. We analyzed the performance in auditory behavioral tests: sound localization (SL), sequential verbal memory (SVM), sequential non-verbal memory (SNVM), frequency patterns (FP), duration patterns (DP), Gap in Noise (GIN), speech in noise (SN), synthetic sentence identification with ipsilateral competing message (SSI ICM) and contralateral competing message (SSI CCM), dichotic digits (DD), staggered spondaic word (SSW) and dichotic nonverbal (DNV), in addition to analyze the results in the School Performance Test (TDE), phonologic and syntactic awareness. The statistical tools used were: t-Test, Mann-Whitney test, Fishers Exact test and the Pearson correlations. Probability values <0.05 were considered statistically significant. Results: Differences between NF1 and control groups were found in the tests: SVM, SNVM, FP, DP, GIN, SN RE and LE, SSI ICM, DD RE and LE, SSW RE and LE, SSI CCM in the LE ratios speech/noise -40 dB, DNV attention to RE and in the phonologic awareness. Positive correlations were observed between the dichotic tests and the school performance subtests. The PF and PD showed positive correlation with the phonologic awareness test. Conclusion: Patients with NF1 displayed auditory processing disorders associated to language and learning disabilities